2016
DOI: 10.1021/acs.jafc.6b04164
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extracellular Expression of Metalloprotease for Z-Aspartame Synthesis

Abstract: Metalloprotease PT121 and its mutant Y114S (Tyr114 was substituted to Ser) are effective catalysts for the synthesis of Z-aspartame (Z-APM). This study presents the selection of a suitable signal peptide for improving expression and extracellular secretion of proteases PT121 and Y114S by Escherichia coli. Co-inducers containing IPTG and arabinose were used to promote protease production and cell growth. Under optimal conditions, the expression levels of PT121 and Y114S reached >500 mg/L, and the extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The stability of the mRNA structure affects the expression level of proteins. A more positive ΔG value of the mRNA secondary structure in the translation initiation region correlates with a higher probability of the translation of mRNA into protein [49]. The obtained ΔG values from the mfold server indicated that 74% of the N-terminal conjugates had higher ΔG values compared with the unconjugated CPG2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of the mRNA structure affects the expression level of proteins. A more positive ΔG value of the mRNA secondary structure in the translation initiation region correlates with a higher probability of the translation of mRNA into protein [49]. The obtained ΔG values from the mfold server indicated that 74% of the N-terminal conjugates had higher ΔG values compared with the unconjugated CPG2.…”
Section: Resultsmentioning
confidence: 99%
“…Crotamin, a toxin found in snake venom, has two nuclear localization domains, named crot (2–18) and crot (27–39). Various derivatives of Crot (27–39) CPP with the original amino acid sequence of “KMDCRWRWKCCKK” are developed using amino acid substitution, deletion, or addition [49]. “Crot (27–39) derivative 7” from our candidate list belongs to this family.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether the addition of TAT sequence to the N‐terminal of TAL has any serious unfavorable effects on the enzyme expression, stability, and function further in silico analyses were employed. The minimum free energy of mRNA translation initiation region and secondary structure have been shown to affect the level of translation 35 . The start codon of TAT‐RsTAL in PET 28a was positioned on the loop, which means that the initiating codon will be more exposed.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum free energy of mRNA translation initiation region and secondary structure have been shown to affect the level of translation. 35 The start codon of TAT-RsTAL in PET 28a was positioned on the loop, which means that the initiating codon will be more exposed. Therefore, higher levels of translation compared with a start codon positioned on the stem can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ΔG and the secondary structure of pET28a linked to mRNA of SP-AvPAL or AvPAL were retrieved. The higher ΔG (the more positive ΔG) indicates the higher expression probability (Zhu et al 2016). According to the results retrieved from the Quickfold server, addition of SP did not always lead to an increase in expression.…”
Section: Prediction Of Mrna Secondary Structure Of Sps and The Mutant Avapl Linked To Pet-28amentioning
confidence: 95%